EFFECTS OF TWO SKILL-BELT MODALITIES ON FRACTION LEARNING FOR 10-YEAR-OLD STUDENTS - Laëtitia DRAGONE; Natacha BUONO; Bruno DE LIEVRE (Universitaria Publishing House, Craiova, 2023)
Learning fractions is important in mathematics education. However, learners have difficulties with this notion. In an attempt to remedy the difficulties encountered by students, we investigate the effect of the modality of obtaining (individual or cooperative) skill belts on the learning of fractions. To our knowledge, the scientific literature offers little information on this topic. This research targets a public of 4th grade primary school learners in a school located in the French-speaking Belgium.